Research on Chinese Solar Photovoltaic Development Based on Green-trading Mechanisms in Power System by Using a System Dynamics Model. (May 2017) - Lyu, Haifang; Li, Hailong; Wallin, Fredrik; Xv, Bin
Abstract: China power year book in 2014 set the target of 300GW of PV installed capacity in 2030. Solar photovoltaic (PV) has shown a significant rise because of green-trading mechanisms. This study focuses on feed in tariff (FIT) and renewable portfolio standard (RPS). The objective of these two policies is attracting the public to invest in and to use solar PV system. Based on the experience of Germany about FIT, this paper aims to evaluate the FIT and RPS policies in promoting installed PV capacity in China. A system dynamics (SD) model of PV system that includes FIT, RPS, PV cost, and installed capacity is built in this study. By using Vensim_DSS software, this paper assesses the effect of different combinations of policies on installed capacity of PV and emission reduction, and finds optimal policy combination. The results show that all four scenarios can reach the target of 300 GW in 2030. The government cost of optimal scenario will be 251 billion RMB less than the scenario of historical trend.